거골 골연골병변 치료 동향: 대한족부족관절학회 회원 설문조사 분석 - 조병기; 조재호; 양기원; 이동연; 배서영; 2021 대한족부족관절학회 학술위원회; Cho, Byung-Ki; Cho, Jaeho; Young, Ki Won; Lee, Dong Yeon; Bae, Su-Young; The Academic Committee of Korean Foot and Ankle Society (대한족부족관절학회지, 2021)
Purpose: Given the lack of definite evidence-based guidelines in clinical practice, there may be a wide variation in treatment protocols for osteochondral lesions of the talus (OLT). Based on the Korean Foot and Ankle Society (KFAS) member survey, this study aimed to report the current trends in the management of OLT. Materials and Methods: A web-based questionnaire containing 30 questions was sent to all KFAS members in September 2021. The questions were mainly related to clinical experience and preferences in diagnosis, conservative, and surgical treatments for patients with OLT. Answers with a prevalence of ≥50% of respondents were considered a tendency. Results: Sixty-two (11.3%) of the 550 surgeons queried responded to the survey. The responses to 9 (30.0%) of the total of 30 questions established a tendency. Answers exhibiting a tendency were as follows; additional diagnostic tools except for plain radiograph (magnetic resonance imaging), most common conservative treatment method (oral medication, rest), most important radiological factor in decision making for surgical treatment and method (size of the lesion, ankle instability, loose bodies), most important patient factors in decision making for surgical treatment and method (age, activity or occupation), infrequently requiring posterior arthroscopy (less than 3%), most common revision surgery for failed bone marrow stimulation procedure (osteochondral autograft transplantation [OAT]), not requiring additional procedure for donor site in OAT, the main reason for unsatisfactory result after OAT (persistent pain without radiological abnormality), no generalization of autologous chondrocyte implantation or chondrogenesis using stem cells. Conclusion: This study presents updated information on current trends in the management of OLT in Korea. Both consensus and variations in the approach to patients with OLT were revealed through this survey. Since recent biologic efforts to regenerate cartilage have been unsuccessful, further studies to identify clinical evidence would be needed.